Formation of amorphous and quasi-two-dimensional microcrystalline structures of CO2 in activated carbon pores at low temperatures. (30th June 2022) - Cons Bacilla, Ana Carolina; Futamura, Ryusuke; Sugiyama, Yasuhiro; Ueda, Takahiro; Iiyama, Taku
Abstract: Carbon micropores are often used for CO2 capture and storage (CCS) applications. In this study, the intermolecular structure of CO2 molecules adsorbed inside activated carbon with different pore sizes was investigated through in situ X-ray scattering measurements, hybrid reverse Monte Carlo (HRMC), and grand canonical Monte Carlo (GCMC) simulations. Although most of the CO2 molecules in the micropores formed an amorphous structure, some formed a microcrystalline structure at certain pore sizes. To determine the structure and stability of this microcrystalline CO2 structure, a systematic structure analysis technique using computational methods was proposed. A plausible quasi-two-dimensional CO2 crystal structure that reproduced the experimental X-ray scattering results was obtained. The structure was found to be stable below 80 K. This microcrystalline structure, which was a characteristic arrangement formed with the assistance of the intrapore potential, was different from that of the bulk CO2 phases. Graphical abstract: Image 1 Highlights: The intermolecular structure of CO2 in activated carbon pores was investigated by in situ X-ray scattering and HRMC analysis. Most CO2 molecules form amorphous structures, and the pore width strongly affects the structure by matching the CO2 size. Some CO2 forms unique quasi-two-dimensional microcrystalline structure in a specific pore width, by the intrapore potentials.